Constitutional principle of unity and division of state power as a fundament for organization and agreed functioning of state bodies in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2021)
The article stands for actual issues for sovereign Kazakhstan, in particular, consideration of the developing relations between highest state bodies: head of state, parliament and government. The clearer their statuses are in the Constitution, as well as the aspiration of the certain polititians and managers to work together for the benefit of the people, the more purposeful, professional and efficient the state is in the implementing its main mission – to ensure human rights and freedoms, also to provide decent life of each individual and the competitiveness of the country. The major focus in the scientific research is put on the basic principles that consider the organization and activities of the system of kazakh state bodies: sovereignty, unity and separation of powers. All of the above will allow you to replenish your knowledge with complex information about the formation and strengthening of constitutionalism, the improvement of specific institutions that support the structure of Independence, also about the genesis and evolution of the state bodies of the Republic of Kazakhstan.Key words: the system of state bodies, sovereignty, the principle of separation of powers, the unity of the system, the system of checks and balances.